Analisis Sistem Informasi Akuntansi Penggajian pada PT XYZ - Kriswanto, Kriswanto (Bina Nusantara University, 2013)
Objectives of this research are to analyze accounting information system in PT XYZ, to analyze payroll process in the company, to identify problems and provide recommendations for improvements to the problems found. Method used in this research trying to build the payroll accounting information system was direct observation in the field, consisting initiation and analysis phase. In the analysis phase, research analyzed the problems that occur in the payroll process. Payroll accounting information system, then, will be proposed to support the internal control over the payroll process, and to facilitate the calculation of salaries. Besides, the system is useful to generate reports relating to payroll processing such as attendance reports to see the amount of employee bonuses gained from the attendance every period, accounts payable, employee tax reports and employee salary reports.